2021
DOI: 10.3389/fnins.2021.632922
|View full text |Cite
|
Sign up to set email alerts
|

Critical Dynamics in Spontaneous Resting-State Oscillations Are Associated With the Attention-Related P300 ERP in a Go/Nogo Task

Abstract: Sustained attention is the ability to continually concentrate on task-relevant information, even in the presence of distraction. Understanding the neural mechanisms underlying this ability is critical for comprehending attentional processes as well as neuropsychiatric disorders characterized by attentional deficits, such as attention deficit hyperactivity disorder (ADHD). In this study, we aimed to investigate how trait-like critical oscillations during rest relate to the P300 evoked potential—a biomarker comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Broadening up to individual differences in overall task performance, in the two studies using a sustained attention task, higher temporal structures in resting-state EEG oscillations were associated with better (Irrmischer et al, 2018B) or worse performance (Herzog, Steinfath & Tarrasch, 2021). In contrast, temporal structure of EEG during the task was associated with worse performance (Irrmischer et al 2018) or not associated with performance (Herzog, Steinfath & Tarrasch, 2021). In conclusion, and similar to the literature on behavioural temporal structure, the literature on neural temporal structures does not currently support clear directional predictions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Broadening up to individual differences in overall task performance, in the two studies using a sustained attention task, higher temporal structures in resting-state EEG oscillations were associated with better (Irrmischer et al, 2018B) or worse performance (Herzog, Steinfath & Tarrasch, 2021). In contrast, temporal structure of EEG during the task was associated with worse performance (Irrmischer et al 2018) or not associated with performance (Herzog, Steinfath & Tarrasch, 2021). In conclusion, and similar to the literature on behavioural temporal structure, the literature on neural temporal structures does not currently support clear directional predictions.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Smit et al (2013) reported only weak correlation between temporal structures in finger tapping series and EEG oscillations during rest, and none with EEG activity recorded during the task. Broadening up to individual differences in overall task performance, in the two studies using a sustained attention task, higher temporal structures in resting-state EEG oscillations were associated with better (Irrmischer et al, 2018B) or worse performance (Herzog, Steinfath & Tarrasch, 2021). In contrast, temporal structure of EEG during the task was associated with worse performance (Irrmischer et al 2018) or not associated with performance (Herzog, Steinfath & Tarrasch, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Smit et al ( 2013 ) reported only weak correlation between temporal structures in finger tapping series and EEG oscillations during rest, and none with EEG activity recorded during the task. Broadening up to individual differences in overall task performance, in the two studies using a sustained attention task, higher temporal structures in resting-state EEG oscillations were associated with better (Irrmischer et al, 2018b ) or worse performance (Herzog et al, 2021 ). In contrast, temporal structure of EEG during the task was associated with worse performance (Irrmischer et al, 2018b ) or not associated with performance (Herzog et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Broadening up to individual differences in overall task performance, in the two studies using a sustained attention task, higher temporal structures in resting-state EEG oscillations were associated with better (Irrmischer et al, 2018b ) or worse performance (Herzog et al, 2021 ). In contrast, temporal structure of EEG during the task was associated with worse performance (Irrmischer et al, 2018b ) or not associated with performance (Herzog et al, 2021 ). In conclusion, and similar to the literature on behavioural temporal structure, the literature on neural temporal structures does not currently support clear directional predictions.…”
Section: Discussionmentioning
confidence: 99%
“…the ability to maintain the balance between stability and flexibility of neuronal assemblies [25]. The utilization of LRTC during resting state as an indicator for adaptability of neural system involving behavior [24], sensory [26] and cognition [27][28][29] became recently evident. Aberrant LRTC has been observed in several psychiatric or neurological pathological conditions: LRTC was stronger in seizure-affected areas in epileptic [30] and depressive patients [31,32].…”
Section: Introductionmentioning
confidence: 99%